Human Atheromatous Plaque Extracts Induce Tissue Factor Activity (TFa) in Monocytes and also Express Constitutive TFa - Muhlfelder, Thomas W.; Teodorescu, Victoria; Rand, Jacob; Rosman, Alan; Niemetz, Julian (Thrombosis and Haemostasis, 1999)
Tissue factor activity (TFa) is a major activator of the coagulation cascade and may play a role in atheroma-induced thrombosis. Mono-cyte-macrophages (MO-MF) generate considerable quantities of TFa when stimulated by a variety of inducers. To test the hypothesis that MO could be induced by atheromatous plaque to generate TFa, plaque extracts obtained from patients with obstructive atheromatous disease were used. These extracts were also assayed for constitutive TFa. The constitutive activity was variable from extract to extract but could be very high, up to 250 U TFa. The TFa induced in MO could be also very high, up to 200 U (i.e. 1/5 of the TFa of full strength rabbit brain thromboplastin). These findings point to a major role for MO-MF TFa in the induction or thrombosis by atheromatous plaque.